STUDY OF PNEUMONIA SEVERITY INDEX AND CURB-65 IN COMMUNITY ACQUIRED PNEUMONIA IN INDUSTRIAL SET-UP - Dr. Sudheer Babu Medide Reddy; Dr. Sachin Y. Gitte; Dr. Shailendra A. Satpute; Dr. Sanket Patil (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background This study was conducted to determine if the pneumonia severity index and CURB-65 are applicable to patients who have community-acquired pneumonia and to investigate the prognostic usefulness of these markers (need for ICU admission and death) in these individuals. Methods This was a hospital-based prospective observational study conducted among eighty patients who were diagnosed to be having community-acquired pneumonia admitted to Hindustan Aeronautics Hospital, over a period of 18 months after obtaining clearance from the institutional ethics committee and written informed consent from the study participants. Results In our study, we observed a significant association between age, ventilator support, inotropes, ICU stay, and mortality with increasing scores in both PSI and CURB-65 scoring systems, demonstrating a high degree of sensitivity and specificity. Whereas the PSI score has a higher prediction for ICU admission and ventilator requirement in CAP patients, the CURB score has a higher prediction for mortality in CAP patients. The ROC curve for ICU admitted patients, patients who received ventilator support, and mortality among CAP subjects was higher for PSI score than CURB-65, that is, PSI score has higher sensitivity, specificity, and area under curve for mortality for all the three aforementioned parameters in CAP patients. Conclusion Both our study’s and the earlier research’s mortality rates in the various risk classes demonstrated that, in both the PSI and CURB-65 risk classes, mortality rates increased steadily as risk scores increased. In predicting ICU admission, ventilator support, inotropic support, and mortality, both PSI and CURB65 have good specificity, with PSI having better sensitivity and specificity than CURB65.